Cell-scale hemolysis evaluation of intervenient ventricular assist device based on dissipative particle dynamics - Xu, Zhike; Chen, Chenghan; Hao, Pengfei; He, Feng; Zhang, Xiwen (Frontiers in Physiology, 2023)
Most of the existing hemolysis mechanism studies are carried out on the macro flow scale. They assume that the erythrocyte membranes with different loads will suffer the same damage, which obviously has limitations. Thus, exploring the hemolysis mechanism through the macroscopic flow field information is a tough challenge. In order to further understand the non-physiological shear hemolysis phenomenon at the cell scale, this study used the coarse-grained erythrocytes damage model at the mesoscopic scale based on the transport dissipative particle dynamics (tDPD) method. Combined with computational fluid dynamics the hemolysis of scalarized shear stress (τ) in the clearance of “Impella 5.0” was evaluated under the Lagrange perspective and Euler perspective. The results from the Lagrange perspective showed that the change rate of scaled shear stress (τ˙) was the most critical factor in damaging RBCs in the rotor region of “Impella 5.0”and other transvalvular micro-axial blood pumps. Then, we propose a dimensionless number Dk with time integration based on τ˙ to evaluate hemolysis. The Dissipative particle dynamics simulation results are consistent with the Dk evaluation results, so τ˙ may be an important factor in the hemolysis of VADs. Finally, we tested the hemolysis of 30% hematocrit whole blood in the “Impella 5.0” shroud clearance from the Euler perspective. Relevant results indicate that because of the wall effect, the RBCs near the impeller side are more prone to damage, and most of the cytoplasm is also gathered at the rotor side.